Prognostic value of aortic regurgitation after TAVI in patients with chronic kidney disease. (15th October 2016) - Possner, Mathias; Vontobel, Jan; Nguyen-Kim, Thi Dan Linh; Zindel, Christoph; Holy, Erik W.; Stämpfli, Simon F.; Zuber, Michel; Kaufmann, Philipp A.; Nietlispach, Fabian; Maisano, Francesco; Niemann, Markus; Tanner, Felix C.
Abstract: Background: Aortic regurgitation (AR) after transcatheter aortic valve implantation (TAVI) for severe aortic valve stenosis results in major haemodynamic changes. Influence of post-implant AR and aortic valve calcification on outcome in patients with chronic kidney disease (CKD) is unclear. Methods: Short-term outcome was defined as a combined 30-day endpoint, long-term outcome as survival. Post-implant AR was classified as none/mild or moderate/severe using transthoracic echocardiography. Aortic valve calcification was calculated by computed tomography. Logistic regression analyses were performed in patients with none/mild (estimated glomerular filtration rate [eGFR] ≥ 30 ml/min/1.73 m 2 ) and advanced (eGFR < 30 ml/min/1.73 m 2 ) CKD to evaluate predictors of outcome and post-implant AR. Results: TAVI was performed in 546 consecutive patients. Moderate/severe post-implant AR was the only independent predictor of the 30-day endpoint in patients with advanced (OR 7.091, 95% CI 1.144–43.962, p  = 0.035), but not in patients with none/mild CKD. Similarly, moderate/severe AR predicted impaired survival only in patients with advanced CKD ( p  < 0.001). NT-proBNP (OR 1.023 per 500 ng/l increase, 95% CI 1.003–1.043; p  = 0.026) before intervention was the only independent predictor of the 30-day endpoint in patients with none/mild CKD. Aortic valve calcification was comparable in patients with none/mild versus advanced CKD and was an independent predictor of moderate/severe post-implant AR in the overall population as well as in the subgroups with none/mild or advanced CKD. Conclusions: Moderate/severe AR after TAVI predicts outcome in patients with advanced CKD, but not in patients with none/mild CKD. Aortic valve calcification is an important predictor of post-implant AR independent of kidney function.